The effects of lidocaine-bupivacaine block in cats undergoing castration - Ng, Tuck Cheok (2015)
The effects of lidocaine-bupivacaine block in cats undergoing routine castration were determined in this controlled, randomized, and blinded study. Twelve cats were randomly assigned to two groups. Cats in Group 1 (Local block, n=6), were given a mixture of 1 mg/kg of 2% lidocaine and 1 mg/kg of 0.5% bupivacaine subcutaneously at the scrotal sac. Cats in Group 2 (Control, n=6) did not receive the local block. Both groups were induced with ketamine-acepromazine intramuscularly, at 15 mg/kg and 0.1 mg/kg respectively, and maintained on sevoflurane via facemask. The systolic (SAP), diastolic (DAP), and mean arterial blood pressure (MAP), heart (HR), and respiratory rate (RR) was measured intra-operatively at specific events. Postoperatively, all cats received meloxicam, 0.2 mg/kg subcutaneously. Pain scores were determined at 4, 8, and 24 hours post-operatively. The mechanical pressure threshold (MPT) values were determined at 2, 4, 8, and 24 hours post-operatively. Intra-operatively, the SAP, DAP, MAP, and HR tended to be higher in the control group. The hemodynamics peaked during traction and autoligation of the first spermatic cord in the control group. There was no treatment difference in RR. Post-operatively, pain scores in the group given local block were lower than the control group at 4 hours post-operation. There is no treatment difference in post-operative HR, RR, SAP, DAP, MAP, and MPT values. Thus, it can be concluded that subcutaneous infiltration of lidocaine-bupivacaine into the scrotal sac before castration improved intra-operative hemodynamic stability, and provided better analgesia up to 4 hours post-castration.